Searching for kindness - Alterkait, Fatima Nabil; Chatterjee, Chaitali (Goodword New Delhi, 2005)
Searching for Kindness is a heartwarming story that follows a character's quest to find and spread kindness in their community, illustrating the transformative power of compassion and the ripple effect of small acts of goodwill.